الترجيح بالسياق القرآني عند ابن جُزَي الكَلبِي من خلال تفسيره التسهيل لعلوم التنزيل: دراسة تطبيقية: A Theoretical and Applied Study of Preference in the Qur’anic Context: A Case Study of al-Tashīl li Ulūm al-Tanzīl By Ibn Juzai Al-Kalbī - Abubakar Muhammad Sani; Shamsuddeen Lawan Yahya (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2026)
Ibn Juzayy al-Kalbi is among the exegesisors distinguished by his concise yet comprehensive approach, thorough investigation, and careful weighing of evidence in his exegesis,